STRATEGI INTEGRASI NILAI PENDIDIKAN AGAMA ISLAM DALAM DESAIN MATERI DAN KURIKULUM DAKWAH ISLAMIYAH - Putri Ruhqhaiyyah Nasution; Nur Syafitri Situmorang; Desi Priaanggina Ritonga (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2026)
This study is motivated by the importance of integrating Islamic Religious Education (PAI) values into the teaching and learning process of Islamic da‘wah, particularly through material design and curriculum development capable of shaping students’ character, religious understanding, and da‘wah competencies holistically. The research employs a descriptive qualitative method with a literature review approach, curriculum document analysis, and data collection through interviews with PAI educators and da‘wah practitioners. The findings indicate that integrating PAI values into the design of learning materials and the Islamic da‘wah curriculum can be achieved through establishing value-based learning objectives, selecting materials relevant to contemporary needs, applying participatory learning strategies, and strengthening evaluation systems based on spiritual and social competencies. The study concludes that material and curriculum designs integrated with PAI values effectively enhance the quality of da‘wah learning, reinforce moral internalization, and encourage students to become knowledgeable, moderate, and well-characterized da‘i. This research recommends the development of an adaptive, contextual Islamic da‘wah curriculum oriented toward 21st-century competencies.